The Relationship Between Work Posture and The Incidence of Low Back Pain Among Laundry Workers in The Area of Campus 1, Muhammadiyah University of Surakarta - Indira Adelina Miyagi; Sri Darnoto (International Journal of Science and Environment (IJSE), 2026)
This study investigated the association between work posture and low back pain (LBP) among Campus 1, Muhammadiyah University of Surakarta laundry workers. A cross-sectional analytical observational design was used to study 50 workers from 36 washing facilities selected by total sampling. The Rapid Entire Body Assessment (REBA) monitored work posture, while a validated Pain and Distress Scale questionnaire measured LBP symptoms. Data was collected from December 2024 to January 2025 and analyzed using univariate and bivariate chi-square tests. REBA found that most workers had low to moderate risk postures, while some had high-risk postures that could cause musculoskeletal diseases. Most LBP complaints were modest, but moderate and severe were notable. A substantial correlation (p < 0.05) exists between work posture and LBP, with higher posture risk leading to more complaints. These findings highlight the importance of ergonomics and preventive interventions in reducing occupational LBP among laundry workers.